Controlled Incorporation of Ni(OH)2 Nanoplates Into Flowerlike MoS2 Nanosheets for Flexible All‐Solid‐State Supercapacitors. (28th August 2014) - Hao, Chunxue; Wen, Fusheng; Xiang, Jianyong; Wang, Limin; Hou, Hang; Su, Zhibin; Hu, Wentao; Liu, Zhongyuan
<x xml:space="preserve">Abstract</x> In this work, self‐supporting three‐dimensional hierarchical nanostructured MoS2@Ni(OH)2 nanocomposites are synthesized via a facile single‐mode microwave hydrothermal technique. The fabricated MoS2@Ni(OH)2 nanocomposites for supercapacitors in aqueous electrolyte exhibit higher specific capacitance and better cyclic stability than those of MoS2 and Ni(OH)2 due to the pronounced synergistic effect between MoS2 and Ni(OH)2. Further, the flexible all‐solid‐state supercapcitor is readily constructed by composing the PVA/KOH gel electrolyte in between two MoS2@Ni(OH)2 electrodes on the flexible PET substrates. The resulting supercapacitors can operate at high rate up to 1000 V/s, have excellent long‐life cycling stability, retaining 94.2% of the initial capacitance after 9000 cycles, and mechanical flexibility during extreme bending, respectively. Thereby, the MoS2@Ni(OH)2 nanocomposites are a promising electrode materials for flexible long‐life cycling all‐solid‐sate supercapacitors.